Nuclear battery-thermocouple type summary report - Murphy, E.L.; Jordan, K. C.; Birden, J.H.; Blanke, B. C.; Mound Laboratory; U.S. Atomic Energy Commission (Miamisburg, Ohio : Mound Laboratory, 1962)
The potential usefulness of approximately 1300 radioactive isotopes as a heat source for the thermoelectric generator was investigated. Eight thermoelectric generators were developed and two of these were used as thermoelectric batteries. Theoretical equations for non-semiconductor thermoelectric materials and experimental measurements to verify the Thompson and Peltier effects are given.
"The object of this contract was to conduct research on radioactive materials and thermocouples suitable for the direct conversion of heat to electrical energy. U.S. Army Signal Corps Contract No. R-65-8-99811-SC-03-91. U.S. Army Signal Research and Development Laboratories Technical Requirement Nos. P.R. and C. 58-ELS/R-3705, 58-ELS/3861 (S). U.S. Department of the Army Project No. 3-99-15-102."
"Mound Laboratory, Miamisburg, Ohio, operated for United States Atomic Energy Commission, U.S. Government Contract no. AT-33-1-GEN-53."
"Date: October 1, 1960 ; Issued: January 15, 1962."
"MLM-1127 ; UC-23 Isotopes--Industrial ; Technology (TID-4500 16th Ed.)."
Includes bibliographical references (p. 67-68).
U.S. Atomic Energy Commission Contract
Keywords: Nuclear energy -- Research -- United States; Thermoelectric generators; Thermocouples; Thermoelectric generators; Thermocouples